Pijat Tangan dan Kaki serta Aromaterapi Lavender untuk Meningkatkan Kualitas Tidur pada Pasien CHF: Studi Kasus - Wiguna, Ilham; Mulyono, Wastu Adi; Andriyana, Andriyana (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2025)
Background: Patients with congestive heart failure (CHF) often experience sleep disturbances, affecting cardiac muscle function, respiration, and immunity. Long-term use of sleeping medication may cause toxicity; thus, non-pharmacological therapies are required. Hand and foot massage combined with Lavender aromatherapy are safe, simple complementary therapies that can improve body circulation and relaxation. However, case studies on the effects of hand and foot massage combined with lavender aromatherapy have not been widely conducted. Objective: To determine the effect of hand and foot massage and Lavender aromatherapy on sleep quality in a CHF patient. Case Report: A 72-year-old male with CHF was hospitalized at Banyumas Hospital, complaining of shortness of breath, productive cough, sleep disturbances, frequent awakenings, fatigue, and changes in day-night sleep patterns. Physical examination revealed blood pressure 150/90 mmHg, respiratory rate 29 breaths/min, pulse 129 bpm, oxygen saturation 90%, and rhonchi breath sounds. Laboratory tests result showed increased Urea, Creatinine, SGOT, SGPT, and blood gas abnormalities (hypoxemia, respiratory alkalosis). Nursing care over three days included sleep education, environmental modification, hand and foot massage, and Lavender aromatherapy. On day one, poor sleep was reported by the patient. On day two, relaxed and improved daytime sleep were noted. On day three, sleep quality improved with longer duration, while reduced dyspnea and coughing were  concluded. Outcome: Intervention improved vital signs, (i.e.blood pressure, hartbeat, respiration, and oxygen saturation) and sleep quality from poor (≥6) to good (≤5). Conclusion: The combination of hand and foot massage with Lavender aromatherapy effectively improve sleep quality in a CHF patient.INTISARILatar belakang: Pasien congestive heart failure (CHF) umumnya mengalami gangguan tidur, menyebabkan terganggunya fungsi otot jantung, pernapasan, dan sistem imun. Toksisitas dapat muncul sebagai akibat dari penggunaan obat tidur secara terus-menerus sehingga dibutuhkan terapi nonfarmakologis. Hand foot massage dan aromaterapi Lavender merupakan terapi komplementer yang aman, mudah diberikan, serta dapat meningkatkan sirkulasi dan relaksasi tubuh. Namun studi kasus tentang pengaruh pijat tangan dan kaki yang dikombinasikan dengan aromaterapi Lavender masih belum banyak dilakukan. Tujuan: Mengetahui bagaimana massage tangan dan kaki serta aromaterapi Lavender dapat memengaruhi kualitas tidur pasien CHF. Laporan kasus: Pasien laki-laki berusia 72 tahun yang menderita CHF dirawat di Rumah Sakit Banyumas. Pasien mengeluhkan sesak napas, batuk berdahak, gangguan tidur, sering terbangun, kelelahan, serta perubahan pola tidur siang dan malam. Pemeriksaan fisik menunjukkan tekanan darah 150/90 mmHg, respirasi 29 kali/menit, nadi 129 kali/menit, saturasi Oksigen 90%, serta suara napas ronki. Hasil laboratorium menunjukkan adanya peningkatan Ureum, Kreatinin, SGOT, SGPT, serta gangguan gas darah (hipoksemia, alkalosis respiratori). Asuhan keperawatan selama tiga hari meliputi edukasi tidur, modifikasi lingkungan, serta intervensi hand foot massage dan aromaterapi Lavender. Hari pertama, pasien melaporkan kualitas tidur buruk. Hari kedua, mulai merasa rileks dengan peningkatan tidur siang. Hari ketiga, kualitas tidur membaik dengan peningkatan durasi tidur dan penurunan keluhan sesak napas, serta batuk. Hasil: Intervensi memberikan perbaikan pada tekanan darah, nadi, respirasi, saturasi Oksigen, serta peningkatan kualitas tidur dari buruk (≥6) menjadi baik (≤5). Simpulan: Hand foot massage dan aromaterapi Lavender efektif dalam memperbaiki kualitas tidur pada pasien CHF.